Optical characterization of different waist diameter on microfiber loop resonator humidity sensor - Jali, Mohd Hafiz; Rahim, Hazli Rafis Abdul; Johari, Md Ashadi Md; Hamid, Sana Sulaiman; Yusof, Haziezol Helmi Mohd; Thokchom, Siddharth; Wang, Pengfei; Harun, Sulaiman Wadi (Elsevier, 2019)
In this paper, the effect of different waist diameter on silica microfiber loop resonator (MLR) relative humidity (%RH) sensor is reported. The silica fiber was tapered to vary the waist diameter to 3 μm, 4 μm, 5 μm,7 μm, 8 μm and 10 μm using flame brushing technique. The MLR with a 300 μm diameter loop was formed by manually twisted the tapered fiber under an optical microscope into a self-touching loop. Initially, the effect of whispering gallery modes (WGMs) on the MLR was observed. Transmission mode spectra were observed to determine the number of resonated wavelength and quality factor (Q-factor). The Q-factor is observed to be >105 for all samples and MLR with 3 μm diameter achieve the highest Q-factor value. A significant response to %RH from 35% to 85% was observed due to the change of refractive index between the MLR and the surrounding medium resulting different light attenuation in the microfiber. The sensitivity increased by a factor of 12.2 for the MLR with diameter of 7 μm as compared to the smaller diameter MLRs and a factor of 13.7 as compared to straight microfiber (SmF). As for resolution, the MLR with waist diameter of 7 μm improve by a factor of 5 as compared to the smaller waist diameter and a factor of 6.5 as compared to SmF. The proposed humidity sensor employs the microfiber loop resonator without any sensitive material coated on it which reduced the complexity during the fabrication and manufacturing process. The reported results may contribute to the optimal waist diameter of microfiber loop resonators for humidity sensing application.